Triumphs and Pitfalls of Leading Social Work Students Through EBP - Lomness, Arielle; Lacey, Sajni (Université d'Ottawa | University of Ottawa, 2018)
Two librarians and a faculty member at UBC Okanagan revitalized the existing IL component in a Master's of Social Work research methodology course. A case-based learning approach was used to facilitate students understanding of the information process for their future social work practice. Interventions and assessments will be shared.